2007
DOI: 10.1177/154193120705100209
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Effects in a Security Inspection Task: Breakdown of Performance Components

Abstract: Data from certified screeners performing an x-ray inspection task for 4 hours, or 1000 images, were analyzed to identify the nature of the vigilance decrement. The expected vigilance decrement was found, with performance measured by probability of detection (PoD) and probability of false alarm [P(FA)] decreasing from hour 1 to hour 4. Correlations between PoD and P(FA) indicate that sensitivity between hours remained the same, however a shift in criterion (Beta) occurred. Significant decreases in both detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In the case of the typical visual search task, this involves reducing the RT per trial by responding faster as TOT increases. Spending less time per trial (i.e., reducing RT) leads to a reduction in target-present responses, which, in turn, leads to a reduction in hits and the false alarms (Ghylin et al, 2007), producing the decrement pattern found in most visual search tasks.…”
Section: Dynamic-allocation Resource Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the typical visual search task, this involves reducing the RT per trial by responding faster as TOT increases. Spending less time per trial (i.e., reducing RT) leads to a reduction in target-present responses, which, in turn, leads to a reduction in hits and the false alarms (Ghylin et al, 2007), producing the decrement pattern found in most visual search tasks.…”
Section: Dynamic-allocation Resource Theorymentioning
confidence: 99%
“…Depending on how false alarms are treated, this can be seen as a speed–accuracy trade-off (SATO). Examples of tasks that induce this alternative pattern of performance decrement include visual search tasks, such as aviation security X-ray visual search (Allan, 2005; Basner et al, 2008; Ghylin, Drury, Batta, & Lin, 2007; Smith, 2006), industrial inspection (Drury, 2015), and search tasks using shapes and other artificial stimuli (Thomson, Seli, Besner, & Smilek, 2014). The pattern in Figure 1b, a decrease in hits and in false alarms, is more consistent with a change in response criterion, indicating a shift to a decision where the observer becomes less willing to make positive responses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings would seem to corroborate the argument that label‐checking, at the very least, draws on similar cognitive processes to visual inspection. However, compared with visual inspection in other industrial domains (e.g., Drury, ; Ghylin et al, ; Jameeson, ; Melchore, ; Rao et al, ; Wang & Drury, ; Wang et al, ), label‐checking would seem to place greater demands on short‐term memory resources (e.g., Cowan, ). This is due to information having to be compared across two sources, namely the label and the product specification sheet which provides details of the retailer's order.…”
Section: Understanding the Demands Of Label‐checking In The Packhousementioning
confidence: 99%
“…Visual inspection tasks are well studied in the ergonomics literature (e.g., Liu & Yu, ), across a range of different industrial, contextual, and organizational settings. These include aircraft inspection (Drury, ); airport X‐ray security inspection (Ghylin, Drury, & Schwaninger, ); telecommunications (Jameeson, ); inspection of small steel cylinders (Kleiner & Drury, ); the use of video magnifiers for inspecting electronic and mechanical components of consumer products (Lee, Man, & Chan, ); pharmaceutical and biological drug products (Melchore, ); contact lens inspection (Rao, Bowling, Khasawneh, Gramopadhye, & Melloy, ); circuit patterns, sheet steel or glass inspection, circuit board comparison (Wang & Drury, ); and simulated solder joint arrays (Wang, Lin, & Drury, ). However, despite the costly nature of human error in this domain, only a small amount of direct research has been carried out on product label‐checking (Smith‐Spark, Katz, Marchant, & Wilcockson, , , ).…”
Section: Introductionmentioning
confidence: 99%